Leveraging Artificial Intelligence to Drive Engagement and Conversions in Social Commerce Platforms - Tykea Khy, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Integrating artificial intelligence (AI) in social commerce represents a transformative force reshaping how businesses engage with consumers and drive conversions in digital marketplaces. This comprehensive article examines AI's technical foundations, implementation strategies, and future directions within social commerce platforms. The article analyzes how sophisticated machine learning algorithms, computer vision technologies, conversational AI, and predictive analytics collectively enhance the shopping experience through personalization and engagement. It further investigates the critical frameworks underlying these technologies, including user profiling systems and dynamic content optimization engines that deliver tailored consumer experiences. As privacy concerns grow, implementing ethical AI practices, including federated learning, differential privacy, and explainable, becomes increasingly vital. Emerging technologies such as multimodal learning, edge AI, augmented reality commerce, and blockchain integration promise to further revolutionize the social commerce landscape, creating more intuitive, transparent, and effective shopping experiences that blur traditional boundaries between social interaction and commerce.
Keywords: Personalization frameworks; conversational AI; computer vision; privacy-preserving techniques; multimodal learning